Coach Leadership Style and Anxiety of West Java Karate Athletes - Ayuningrum, Eka; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
Anxiety in athletes is a problem that has not been resolved by coaches, especially in the sport of karate. The leadership style that a coach has is one of the factors that can cause anxiety in athletes. This research aims to examine the relationship between a coach's leadership style and athlete anxiety, and to find out what kind of leadership style really influences athlete anxiety. Using descriptive methods, and a quantitative research approach, with a correlational research design which involves collecting data to determine whether there is a relationship between the two variables. The sample in this study involved 15 West Java karate athletes (8 women, 7 men). By using a questionnaire in the form of SAS-2 (Sport Anxiety Scale) and Leadership Scale for Sport (LSS) which athletes fill out via Google form. The results of the study showed that there was a significant relationship between the coach's leadership style and the anxiety of karate athletes. The conclusion of this research is that the coach's leadership style and anxiety are two things that are related to each other, so both need to be considered in the process of coaching karate athletes. Therefore, the author suggests coaches pay more attention to their athletes' anxiety levels.